REMEDIASI MISKONSEPSI SISWA MENGGUNAKAN MODEL DIRECT INSTRUCTION BERBANTUAN ANIMASI FLASH PADA MATERI TUAS - Sari, Dinda Intan Permata; Sitompul, Stepanus Sahala; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractRemediation students? misconceptions using direct instruction models by flash animation on the lever material was aims of this pre-experimental design with one group pretest-posttest design reserarch. Nine questions of the test was formed by multiple choice that representative CRI Method given to VIII G Class SMP N 1 Sungai Raya. This research discovered that direct instruction models using flash animation decrease students? misconseption. One student had increased larger number of misconception (2 concepts) and one student had not change at all. Remedation by direct instruction model using flash animation effective (d=1.70) to decrease student misconseption. The result of this research is expected to be used as one of remediation alternative on lever material. Key words : Remediation, lever, direct instruction, flash.